Integrated shoe upper system for accessing dorsal pressures in the diabetic foot: A preliminary approach - Martins, Pedro (2022)
Diabetic foot is one of the most serious complications affecting the feet of diabetic patients; These patients begin to lose protective skin sensitivity in their feet and are at risk for trauma, infection, ulceration and, in more serious cases, amputation.